2021
DOI: 10.1021/acs.jafc.0c07771
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins Are Converted into Anthocyanidins and Phenolic Acids and Effectively Absorbed in the Jejunum and Ileum

Abstract: Anthocyanins have been known for their health benefits. However, the in vivo digestion and absorption of anthocyanins through the gastrointestinal tract have not been fully clarified, creating challenges for understanding why anthocyanins have high biological activities and purported low bioavailability in vivo. Twenty-seven male rats were intubated with a 500 mg/kg dose of cyanidin-3-glucoside (C3G). Samples from rats’ stomach, duodenum, jejunum, ileum, colon, and serum were collected at 0.5, 1, 2, 3, 4, 5, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…C3G has been reported to be mainly absorbed through the stomach, duodenum, jejunum, and ileum, and with the extension of time, the content of C3G in urine decreased rapidly, , which may explain why the ACR adducts of C3G were not detected in mouse and human urine.…”
Section: Results and Discussionmentioning
confidence: 99%
“…C3G has been reported to be mainly absorbed through the stomach, duodenum, jejunum, and ileum, and with the extension of time, the content of C3G in urine decreased rapidly, , which may explain why the ACR adducts of C3G were not detected in mouse and human urine.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In several studies performed in humans using a variety of anthocyanin-rich sources, the concentration of plasma compounds in the range of 6-2400 mg has been reported [97,[104][105][106][107]. Similarly, an in vivo study in rats showed the presence of ANs in the stomach at a concentration of 2013.2 ± 280.2 µM at 0.5 h after administration of a dose of 500 mg/kg dose of Cy-3-glucoside [108]. Moreover, the absorption of 23.0 nmol of ANs was recorded 30 min after the injection of a concentration of 70.9 nmol in the gastric lumen of rats [101].…”
Section: Ans Bioavailabilitymentioning
confidence: 94%
“…Moreover, it is well-known that glycosylated polyphenols, such as quercetin-3- O -β- d -glucoside, quercetin-4′- O -β- d -glucoside, and rutin are absorbed as their aglycon forms and phenolic metabolites as a result of hydrolysis by the gut microbiota and/or intestinal enzymes. ,, Thus, anthocyanins, which are originally glycosides, may be hydrolyzed into the aglycon forms and phenolic metabolites in the intestinal tract after their intake and exert varying bioactivities. These findings also strongly suggest the importance of investigating the absorption and bioavailability of anthocyanins to evaluate the mechanism of their biological action.…”
Section: Introductionmentioning
confidence: 99%